Is Our Food Safe from Pesticides? - Frederick M. Fishel (EDIS)
Growers of the food supply have adopted the use of integrated pest management (IPM) because it is no longer possible to rely solely on chemical pesticides to prevent unacceptable crop losses. According to the U.S. Environmental Protection Agency (EPA), IPM is the coordinated use of pest and environmental information and available pest control methods to prevent unacceptable levels of damage by the most economical means with the least possible hazard to people, property, and the environment. Scientific IPM strategies give the grower economic incentives for sustaining long-term crop protection with minimal disruption to the environment. The agricultural community typically will use pesticides sparingly as part of the IPM strategy whenever proven alternatives are not available for pest control. This 4-page fact sheet was written by Frederick M. Fishel, and published by the UF Department of Agronomy, March 2013.